2022
DOI: 10.3389/fsoil.2022.824087
|View full text |Cite
|
Sign up to set email alerts
|

Post-termination Effects of Cover Crop Monocultures and Mixtures on Soil Inorganic Nitrogen and Microbial Communities on Two Organic Farms in Illinois

Abstract: Cover crops can continue to affect agricultural systems even after they have been terminated by influencing nitrogen dynamics and by altering soil microbial communities. These post-termination effects can influence soil fertility, weed pressure, and the dynamics of potential plant pathogens in the narrow window of time between cover crop termination and cash crop emergence. We evaluated the post-termination effects of 12 different spring-sown cover crop mixtures and monocultures on soil nitrogen and microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…Still cover crops can influence the soil microbiome. Aiyer et al (2022) showed that the choice of cover crop, including ryegrass, in combination with the cash crop barley changed the soil fungal and bacterial community but Lucadamo et al (2022) argued the cover crop influence to be weak. According to a meta-analysis, plants generally used as cover crops increased parameters of soil microbial abundance, activity, and diversity by 27%, 22%, and 2.5% respectively, compared to those of bare fallow (Kim et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Still cover crops can influence the soil microbiome. Aiyer et al (2022) showed that the choice of cover crop, including ryegrass, in combination with the cash crop barley changed the soil fungal and bacterial community but Lucadamo et al (2022) argued the cover crop influence to be weak. According to a meta-analysis, plants generally used as cover crops increased parameters of soil microbial abundance, activity, and diversity by 27%, 22%, and 2.5% respectively, compared to those of bare fallow (Kim et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Le Clair, a filamentous anamorphic species belonging to the Basidiomycota phylum. M. polyspora has been widely isolated in agricultural soils worldwide and found to be overrepresented in the tilled soil (Klaubauf et al, 2010 ; Panelli et al, 2017 ; Lucadamo, 2018 ; Longley et al, 2020 ; Větrovský et al, 2020 ; Orrù et al, 2021 ). This species presents several traits such as rapid growth, low requirement of nitrogen, ability to concentrate important biogenic macroelements (N, P, S, K, and Ca) and translocate nutrients, metabolic plasticity, and the production of antibiotic and antifungal compounds (triene compounds), which make it an efficient pioneer colonizer (Beale and Pitt, 1995 ; Pinzari et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The β-glucosidase activity was highest in diversi cation (D) due to availability of easily decomposable organic matter that triggers the β-glucosidase activity in soil (Silva the organic matter. This retention raises a conducive environment for bene cial soil microbes that enhance nitrate reduction through denitri cation(Lucadamo et al 2022).…”
mentioning
confidence: 99%